CQPWeb: Uma nova plataforma de pesquisa para o CRPC - Mendes, Amália (2012)
We present a newly available online resource for Portuguese, a new version of the Reference Corpus of Contemporary Portuguese, now searchable via a user-friendly web interface. We report on work carried out on the corpus previous to its publication online, namely how the corpus was built, our choice of metadata and the processes and tools involved for the cleaning, preparation and annotation to make the corpus suitable for linguistic inquiries. We also describe the web platform and resume the extensive search options available for linguistic or NLP studies.